ESTIMATING GROUND SETTLEMENT POST-LIQUEFACTION USING CPT - Agus Setyo Muntohar (Fakultas Teknik Sipil UII, 2010)
The Universitas Muhammadiyah Yogyakarta (UMY) campus is constructed on 28 hectare which mostly rested on a sand deposit layer and the ground water table was shallow relatively. During earthquake on May 27, 2006, a magnitude 6.3 struck the provinces of Yogyakarta resulted in number of seismic damages were reported. The damages were identified because of liquefaction phenomena during the ground vibration. Reconnaissance study after the earthquake was found some sand boiling sites near the Masjid and Library building. This paper presents liquefaction evaluation and estimation of liquefaction- induced settlement at those building. The liquefaction analysis is based upon force equilibrium concept using cone penetration test (CPT) method. The ground settlement is calculated from CPT data which were collected from 9 testing sites at those studied area. The computation shows that the ground accelerations will make more than 50% of top sand layer liquefied at Library building. In general, the estimated ground settlement ranges from 2.5 cm to 13.5 cm at the hazard area. The results imply that ground improvement should be applied to reduce the effect of liquefaction-induced ground settlement. After three days of lime-column intallation, the settlement is lower that the tolerable settlement.